FIRST REPORT AND PREVALENCE OF SESSILE CILIATE (Vorticella sp.) IN CULTURED Clarias gariepinus IN NIGERIA - OKUNADE, O. A; AJANI, E. K.; ADEJINMI, J. O.; OLADOSU, G. A. (Nigerian Journal of Fisheries, 2021)
Fish parasites commonly cause portal for secondary infections, hindering high productivity leading to economic loss in fish production. Protozoan parasites are a significant group of pathogens affecting cultured fish. The present study was carried out to investigate the prevalence of parasites infecting different stages of cultured Clarias gariepinus in Lagos State. A total of 487 cultured Clarias gariepinus were collected randomly from different culture facilities in culture systems and parasitological examinations were conducted on them. Identification keys with morphometric criteria were used to identify Vorticella sp from other sessile ciliates. Vorticella sp. was observed on the skin and intestine. It was found in all the culture systems and developmental stages. The highest prevalence for Vorticella sp. was found on adult skin (12.84%) and intestines (3.85 %). The mean intensity of Vorticella sp. was highest on fingerlings skin (23.88) and juvenile intestine (16). The mean water parameters showed a suitable range for their survival. This study is the first report of this sessile ciliate in Nigeria, indicating that more parasites are yet undiscovered in aquaculture.